Hungary : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2004)
This Selected Issues paper reviews indicators for external competitiveness in Hungary. The paper examines recent developments in a range of indicators. These include regional comparisons of wage and unit labor cost developments, and standard indicators based on price and cost-based measures of the real effective exchange rate (REER). In addition, the paper discusses actual export performance and market shares, profitability indicators, and business survey results. The equilibrium exchange rate is estimated. The paper also analyzes financial sector regulatory governance in Hungary.